High-level ab initio computations of the absorption spectra of organic iridium complexes - Plasser, Felix; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2015)
The excited states of fac-tris(phenylpyridinato)iridium [Ir(ppy)3] and the smaller model complex Ir(C3H4N)3 are computed using a number of high-level ab initio methods, including the recently implemented algebraic diagrammatic construction method to third-order ADC(3). A detailed description of the states is provided through advanced analysis methods, which allow a quantification of different charge transfer and orbital relaxation effects and give extended insight into the many-body wave functions. Compared to the ADC(3) benchmark an unexpected striking difference of ADC(2) is found for Ir(C3H4N)3, which derives from an overstabilization of charge transfer effects. Time-dependent density functional theory (TDDFT) using the B3LYP functional shows an analogous but less severe error for charge transfer states, whereas the ωB97 results are in good agreement with ADC(3). Multireference configuration interaction computations, which are in reasonable agreement with ADC(3), reveal that static correlation does not play a significant role. In the case of the larger Ir(ppy)3 complex, results at the TDDFT/B3LYP and TDDFT/ωB97 levels of theory are presented. Strong discrepancies between the two functionals, which are found with respect to the energies, characters, as well as the density of the low lying states, are discussed in detail and compared to experiment.
Gesehen am 08.12.2017